Population status of endemic tree kokoleceran (Vatica bantamensis) in Ujung Kulon National Park, Indonesia - IYAN ROBIANSYAH; DODO DODO; ARIEF HAMIDI (Society for Indonesian Biodiversity, 2019)
Abstract. Robiansyah I, Dodo, Hamidi A. 2019. Population status of endemic tree kokoleceran (Vatica bantamensis) in Ujung Kulon National Park, Indonesia. Biodiversitas 20: 296-302. Kokoleceran (Vatica bantamensis) is an endemic tree found only in Ujung Kulon National Park (UKNP), Banten, Indonesia, and is classified as Endangered by IUCN Red List. To develop effective conservation measures of threatened plants, current information on population status and distribution of the species is needed. Thus in the present study, a targeted survey of kokoleceran was conducted in UKNP aiming at mapping the distribution of the species, measuring current population size and structure, assessing the habitat preferences, and identifying threats to the species. Using a non-random adaptive cluster sampling, a total of 27 clusters harboring 280 individuals of kokoleceran was located, of which 20 % were in mature stage. All these individuals were only found in Mount Payung and its surrounding areas, and formed an inverse-J-shaped population structure pattern. The species was estimated to have an area of occupancy and extent of occurrence of 8 km2. The invasive langkap palm (Arenga obtusifolia, Arecaceae) was identified as the main threat for kokoleceran. Based on these results, kokoleceran appears to more than justify its conservation status of Critically Endangered B1ab(iii,v) +2ab(iii,v); C2a(ii).